El enterramiento ibérico de la " crátera de la Grifomaquia" de Orleyl - Melchor Monserrat, José Manuel; Ferrer, J.J.; Benedito Nuez, Josep (Millars. Espai i Història, 2010)
This article presents new data on the gryphomacy krater burial in the Iberian necropolis of Punta d’Orleyl, in la Vall d’Uixó (Castellón, Spain). The krater was discovered at the end of the 1970s. We have carried out a revisionist study of this krater and the accompanying grave goods by analysing several parallel cases from Italy and the Iberian Peninsula.